2015
DOI: 10.1016/j.jcrimjus.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging research on psychopathy: Implications for punishment, prediction, and treatment in youth and adults

Abstract: While there has been an exponential increase in brain imaging research on psychopathy in the past two decades, knowledge on the brain basis to child and adolescent psychopathic-like behavior is relatively new. This adult and child research has potential future implications for the development of new interventions, prediction of future offending, and punishment. This review examines both adult and child literatures on the neural basis of psychopathy, together with implications for the criminal justice system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 137 publications
3
40
0
1
Order By: Relevance
“…One of the most prominent neurobiological models of psychopathy focuses on dysfunctions in amygdala and ventromedial prefrontal cortex (vmPFC) (Anderson & Kiehl, 2012;Blair, 2006;Korponay et al, 2017). Imaging studies have been providing evidence for amygdala and prefrontal deficits in psychopathy (Blair, 2008;Kiehl et al, 2001;Koenigs, 2012;Motzkin et al, 2011;M€ uller et al, 2003;Philippi et al, 2015;Umbach et al, 2015;Yoder et al, 2015). The amygdala is important for the processing of emotionally salient information including threatening emotions and fear (Davis & Whalen, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prominent neurobiological models of psychopathy focuses on dysfunctions in amygdala and ventromedial prefrontal cortex (vmPFC) (Anderson & Kiehl, 2012;Blair, 2006;Korponay et al, 2017). Imaging studies have been providing evidence for amygdala and prefrontal deficits in psychopathy (Blair, 2008;Kiehl et al, 2001;Koenigs, 2012;Motzkin et al, 2011;M€ uller et al, 2003;Philippi et al, 2015;Umbach et al, 2015;Yoder et al, 2015). The amygdala is important for the processing of emotionally salient information including threatening emotions and fear (Davis & Whalen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A study based on independent component analysis (ICA), a data-driven approach, found significant associations between psychopathy scores and functional connectivity in three networks including the default mode network, frontoparietal network, and visual network in fMRI data collected during an auditory oddball task (Juarez, et al, 2013). A review on brain imaging research on psychopathy by Umbach and collaborators empathizes the need of exploration of other brain regions and circuits besides the amygdala and prefrontal cortex that may give rise to different features of psychopathy (Umbach, et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Psychopathy seems necessary, though not sufficient, for explaining the causal mechanisms associated with chronic, serious, and violent (CSV) offending trajectories. The articles in this special issue illustrate both strengths and weaknesses concerning psychopathy and (a) its integration into existing criminological theories (DeLisi & Vaughn, 2015;Fox, Jennings, & Farrington, 2015) and neuropsychological models of offending (Umbach, Berryessa, & Raine, 2015), (b) its use as a risk factor for the development of offending over time Walters, 2015), and (c) its use as a risk factor for specific types of offenders, including female offenders (Forouzan & Nicholls, 2015), institutional offenders (Shaffer, McCuish, Corrado, Behnken, & DeLisi, 2015), sexual offenders (Cale, Lussier, McCuish, & Corrado, 2015), and violent offenders . Given the research in this special issue and elsewhere (e.g., DeLisi, 2009;DeLisi & Piquero, 2011;Vaughn, Howard, & DeLisi, 2008), we believe that the construct is necessary, though not sufficient, for identifying causal mechanisms underlying CSV offending trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Copious research findings have shown that psychopathy is significantly associated with an array of antisocial and other problem behaviors, including conduct problems, delinquency, externalizing symptoms, crime, and violence. Due to the numerous studies that have found a link between low physiological arousal and antisocial behavior [4,5,6,13], it is somewhat surprising that little research has examined the relations between low physiological arousal and psychopathy facets. At the very least, it seems plausible that low physiological arousal should be related to the affective dimensions of juvenile psychopathy such as Callous-Unemotionality and Uncaring.…”
mentioning
confidence: 99%